2014
DOI: 10.1111/cea.12306
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of young adult wheeze: a cluster analysis in a longitudinal birth cohort

Abstract: Background Cluster analyses have enhanced understanding of the heterogeneity of both paediatric and adult wheezing. However while adolescence represents an important transitional phase, the nature of young adult wheeze has yet to be clearly characterised. Objectives To use cluster analysis to define, for the first time, clinically relevant young adult wheeze clusters in a longitudinal birth cohort. Methods K-Means Cluster analysis was undertaken among 309 currently wheezing subjects at 18-years in the Isle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
(95 reference statements)
0
10
0
Order By: Relevance
“…This indicates that having asthma or AD as a single disease may not be driven by IgE. A cluster analysis of wheeze in 18‐year‐olds from the IoW cohort showed that 25% of children with wheezing fell within the adolescent‐onset low‐atopy wheeze cluster that was predominated by females . We included asthma and not only wheezing, but the asthma‐only group shared some of the same characteristics: low frequency of sensitization, predominance of girls, and the majority with a late onset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that having asthma or AD as a single disease may not be driven by IgE. A cluster analysis of wheeze in 18‐year‐olds from the IoW cohort showed that 25% of children with wheezing fell within the adolescent‐onset low‐atopy wheeze cluster that was predominated by females . We included asthma and not only wheezing, but the asthma‐only group shared some of the same characteristics: low frequency of sensitization, predominance of girls, and the majority with a late onset.…”
Section: Discussionmentioning
confidence: 99%
“…A study from MeDALL (Mechanism of the Development of ALLergy) published in 2014 stated that coexistence of eczema, rhinitis, and asthma in the same child is more common than expected by chance irrespective of IgE sensitization . Studies have shown that the presence of sensitization has a major influence on the development and course of childhood conditions such as asthma and rhinitis . However, adolescence is a period of dynamic physiological changes that may influence the development of atopic diseases , where the presence of sensitization could be less important .…”
mentioning
confidence: 99%
“…This relationship emerged also in UK and US studies where active smoke was a risk factor for undiagnosed wheeze at 18 years old (OR 2.54 and OR 2.60, respectively) [ 39 , 41 ]. In a recent paper about the same UK sample, subjects identified as “undiagnosed-wheezers” phenotype had the highest prevalence of smoking habit (74.6%) with respect to the other “wheezers” phenotypes [ 42 ]. A possible explanation is that respiratory symptoms, such as wheeze or breathlessness, are misinterpreted as due to smoking, rather than referred to asthmatic condition and, thus, not reported to the physician.…”
Section: Discussionmentioning
confidence: 99%
“…Yet clinical studies show wide heterogeneity to asthma both across the life course and at different levels of asthma severity. 25,[80][81][82] It is also clear that a proportion of patients with asthma do not attain good asthma control with current treatments. This failure to deliver good asthma control with current approaches was the focus of a Lancet 2017 Commission "After asthma: redefining airways disease".…”
Section: The Treatable Traits Paradigm -Difficult-to-control Asthma As a Multimorbidity Difficult Breathing Syndromementioning
confidence: 99%